Demonstrasi Kehadiran Protein Permukaan Sel Yang Antigenik Dan Spesifik Untuk Shigella Spp. Dan Pembangunan Ke Arah Ujian Diagnostik Segera Bagi Penyakit Shigelosis - Kirnpal Kaur, Banga Singh (2001)
Shigella spp. is the major etiologic agent of dysentery or bloody diarrhoea in humans. It has been identified as an important cause for morbidity and mortality among children especially in developing countries. Early diagnosis of shigellosis is the major strategy for limiting this highly contagious disease. Since routine culturing and bacterial determination from patients' faeces are laborious, timeconsuming, relatively expensive and of low sensitivity, the development of a more rapid and simplified diagnostic test for shigellosis is highly desirable. The test must be sensitive, specific, easy to perform, cost-effective and be able to detect the presence of Shigella spp. directly from patients' specimen especially faeces. As such, the objective of this study was to determine the presence of a specific and antigeniC protein for Shigella spp. and to use it for the development of a rapid diagnostic test for shigellosis.